Processo de destilação simples aplicado como alternativa de pré-tratamento para lixiviado de aterro sanitário - Canabarro, Mariana Islongo (2022)
Many of the existing technologies for the treatment of leachate from landfills are not always able to achieve a satisfactory efficiency in the removal of pollutants. Thus, the simple distillation process is suggested in this master's proposal as a pre-treatment alternative for a landfill leachate. The distillation process consists of the technique of separating more volatile components from less volatile ones, by means of heating and partial vaporization followed by condensation. Among the existing techniques, distillation deserves to be highlighted for not using coagulants or chemical products and, consequently, for not generating large amounts of excess sludge at the end of the treatment. Thus, this work aimed to evaluate the efficiency of the distillation process as an alternative pre-treatment for leachate. To carry out the tests, samples of raw and concentrated leachate were collected at the Santa Maria landfill, in Rio Grande do Sul. The samples were submitted to the simple distillation process set up at the Environmental Engineering Laboratory at the Federal University of Santa Maria. During the process, the parameters of temperature, process time and amount of distilled leachate were monitored, in order to obtain the optimal conditions for the distillation of the leachate. After the first 30 minutes of testing, with an average heating mantle temperature of 265ºC, it is possible to notice the beginning of the distillate production, which is visually colorless. The possibility of being able to incorporate this technique into a sanitary landfill plant, using the gas generated by the degradation of waste as a source of energy to start the process, is very promising, innovative and sustainable. It is important that after treatment, the effluent meets the discharge standards for liquid effluents established by CONAMA Resolutions No. 430/2011 and CONSEMA No. 355/2017, which was achieved after applying the distillation process as a pre-treatment step. In addition, ecotoxicological tests were carried out with Eisenia andrei earthworms, using the crude distilled leachate. The objective of the bioassays was to evaluate the toxicity of the treated effluent to an organism of the terrestrial ecosystem in the event of a spillage/leakage in the soil. However, the results were somewhat inconclusive, due to the occurrence of deaths in the control treatment. A reason for such behavior can be attributed to the non-feeding of organisms during the exposure period.